Audit in Russian Federation and the Research Toward the Determination of the Functioning of Audit Mechanism - Akgün, Leyla; Tektüfekçi, Fatma (Asian Journal of Economic Modelling, 2016)
Although the development of audit laws in Russia corresponds to the end of the 80s, there has been experienced significant progress in this respect in the early 2000s. Since the early 2000s, many laws have been developed and many local auditing standards have been prepared in the country by benefiting from the international experience. Since 2010, the government control over the audit activity began to decline. In this study, information about the legal regulations implemented in Russia has been provided. Subsequently, basic indicators pertaining to the audit for the years 2013-2014 such, as the number of auditors and audit firms, distribution services volume by the auditing company, the number of audited companies, the revenue structure of the audit firms and regional distribution of audit firms, has been discussed and the impact of legislation on audit activity was investigated. Data related to the audit, are based on information published by the Russian Ministry of Finance.